Investigating the role of GLUL as a survival factor in cellular adaptation to glutamine depletion via targeted stable isotope resolved metabolomics - Bayram, Șafak; Razzaque, Yasmin Sophiya; Geisberger, Sabrina; Pietzke, Matthias; Fürst, Susanne; Vechiatto, Carolina; Forbes, Martin; Mastrobuoni, Guido; Kempa, Stefan (Frontiers in Molecular Biosciences, 2022)
Cellular glutamine synthesis is thought to be an important resistance factor in protecting cells from nutrient deprivation and may also contribute to drug resistance. The application of ‘targeted stable isotope resolved metabolomics’ allowed to directly measure the activity of glutamine synthetase in the cell. With the help of this method, the fate of glutamine derived nitrogen within the biochemical network of the cells was traced. The application of stable isotope labelled substrates and analyses of isotope enrichment in metabolic intermediates allows the determination of metabolic activity and flux in biological systems. In our study we used stable isotope labelled substrates of glutamine synthetase to demonstrate its role in the starvation response of cancer cells. We applied 13C labelled glutamate and 15N labelled ammonium and determined the enrichment of both isotopes in glutamine and nucleotide species. Our results show that the metabolic compensatory pathways to overcome glutamine depletion depend on the ability to synthesise glutamine via glutamine synthetase. We demonstrate that the application of dual-isotope tracing can be used to address specific reactions within the biochemical network directly. Our study highlights the potential of concurrent isotope tracing methods in medical research.